1982
DOI: 10.1080/00103628209367327
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soil ph on the activity of oryzalin and metribuzin on five common weeds in no‐till crop production

Abstract: Metribuzin [4-amino-6-tert-buty1-3-(methylthio)-as-triazi ne-5(4H)-one] and oryzalin (3,5-dinitro-N 4 N 4 -dipropylsufanilamide) at two rates each were applied to pots of Cecil sandy loam soil adjusted to pH levels of 5.8, 6.2, 6.8, and 7.2 containing five weed species. Redroot pigweed (Amaranthus retroflexus L.) and large crabgrass [Digitaria sanguinalis (L.) Scop.] were completely controlled by both herbicides at all rates and all pH levels. Sicklepod (Cassia obtusifolia L.) was controlled by metribuzin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In greenhouse studies, increased soil pH increased activity of metribuzin against perennial ryegrass (Lolium perenne L.) (16) and several broadleaf weeds (17). The increased activity of both herbicides at increased pH could result from increased herbicide availability due to decreased adsorption or to increased herbicide absorption.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In greenhouse studies, increased soil pH increased activity of metribuzin against perennial ryegrass (Lolium perenne L.) (16) and several broadleaf weeds (17). The increased activity of both herbicides at increased pH could result from increased herbicide availability due to decreased adsorption or to increased herbicide absorption.…”
Section: Resultsmentioning
confidence: 99%
“…Soil pH may affect the phytotoxicity of a herbicide by changing the ionic character of the herbicide, the magnitude and nature of the charge on soil clays and organic matter; or the absorption of the herbicide by plant roots. Increased soil pH decreased activity of aliphatic acids, bipyridyliums, and thiocarbamates (S), while increased phytotoxicity at increased soil pH has been observed with phenoxyaliphatic acids (5), dinitroanilines (9,17), and s-triazines (4,9,23). The increased phytotoxicity of j-triazines at increased soil pH has been attributed to reduced adsorption of these herbi cides at higher pHs on soils (4), clay minerals (6,21), and organic matter (13,24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This characteristic is valuable in preventing leaching into the lower regions of the container where it may cause damage to crop roots or exit the containers into nursery runoff water. Previous research has indicated that the weed control activity of oryzalin increased with increasing soil pH (Robinson 1982). Taking these chemical and other studies about oryzalin soil behavior (Gingerich and Zimdahl 1976;Harvey 1974) into consideration, indications are that oryzalin hysteresis occurs without loss of herbicidal activity.…”
mentioning
confidence: 99%